Experiences in Developing Tidal Current and Wave Energy Devices for Mediterranean Sea - Coiro, Domenico P.; Troise, Giancarlo; Bizzarrini, Nadia (Frontiers in Energy Research, 2018)
In the last years, the interest for renewable energies has shown a continuously increasing trend, in search of a convenient and sustainable source alternative to carbon and fossil fuels, also due to government incentive systems, as can be seen for example in the objectives proposed by the EU 2020 target. In such context, marine energy sources are particularly attractive, both for the high conceptual available resource and for some specific technical characteristics, such as a more predictable behavior with respect to other sources like wind energy. The work here presented resumes the experience gained over more than twenty years of activities conducted at Department of Industrial Engineering of the University of Naples “Federico II”, in collaboration with research consortium Seapower scrl, in the field of ocean renewable energies. The work refers to several case reports related to different projects in which the research group has been involved. Two main energy sources have been investigated, namely tidal currents and wave energy, through the development, among others, of two different projects reported in this paper: • GEMSTAR: a submerged floating tidal current hydrokinetic turbine system (an evolution of GEM turbine) • PIVOT: a wave energy converter based on a pivoting buoy GEMSTAR is a project which is at Technology Readiness Level (TRL) 7 being the first prototype tested in real field while PIVOT is at TRL 5 since the full-scale prototype has been tested only in controlled environment. In any case both projects are still in development, evolving to more mature technology levels. The article reports the two case studies related to the above-mentioned systems at the present development stage along with the resource assessment of both energy sources in Mediterranean area.